Correlation Between Nutritional Knowledge and Nutritional Status on Students' Academic Achievement - Fatma Dhafir; Abd. Hakim Laenggen; Masriani Masriani; Lilies Tangge; Rafiqa Rafiqa; Saripa Husnul Qhatimah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This study investigates the relationship between nutritional knowledge, nutritional status, and academic achievement among junior high school students. Nutrition plays a vital role in cognitive performance, influencing concentration, memory, and energy levels. A cross-sectional correlational study was conducted at SMP Negeri 14 Palu, Central Sulawesi, involving 60 students across grades VII to IX. Data were collected using a structured questionnaire, anthropometric measurements, and academic performance records. Bivariate analysis using the Gamma correlation test revealed a statistically significant positive relationship between nutritional knowledge and academic achievement (Gamma = 0.515; p = 0.003). Conversely, a significant negative correlation was observed between nutritional status and academic performance (Gamma = –0.543; p = 0.040). These findings underscore the importance of structured nutrition education in supporting academic outcomes, while also highlighting the complex, non-linear relationship between physical health indicators and cognitive performance.